Experience with blood purification therapy with oXiris® hemofilter for the management of septic shock secondary to acalculous cholecystitis: a case report - Kam, Zhi Yuan; Ghazali, Abdul Majid; Mohd Nor, Mohd Basri (2023)
Acute acalculous cholecystitis (AAC) is an acute inflammatory disease of the gallbladder without the presence of gallstones. It is characterized by atypical clinical manifestations, including a complex aetiology, rapid onset, and rapid disease progression. The pathogenesis of AAC is multifactorial, involving anatomical and functional factors that can lead to gallbladder ischemia, bile excretion disorder, cholestasis, and secondary bacterial infection. Critically ill patients, such as those in a coma, requiring endotracheal intubation, using sedatives and analgesics, or unable to communicate or cooperate with physical examinations due to primary diseases, are commonly affected by AAC. Due to the rapid onset and progression of the condition, prompt intervention is necessary following diagnosis. (1) According to the 2018 Tokyo guideline for acute cholecystitis, patient presenting with septic shock and multiorgan involvement is categorized as severe (Grade III). In view of the patient’s inability to tolerate surgery, conservative management was undertaken for patient. (2) At the biochemical level, cytokine markers including tumour necrosis factor (TNF)- α, interleukin (IL)-6, and IL-10 were significantly higher in septic shock. (3) Based on this knowledge of the host immune response mechanism during sepsis, extracorporeal blood purification therapies have been proposed as an alternative treatment. Various techniques are available, including high adsorption hemofiltration such as the oXiris® hemofilter. Besides providing renal support, this haemofilter also aids in the removal of cytokine, endotoxin, and inflammatory mediators.(3) Here, we present the successful treatment of a patient with septic shock secondary to acute acalculous cholecystitis with AKI using CVVHdf with oXiris® hemofilter.